Decreased Cardiovascular Risk after Roux-en-Y Gastric Bypass Surgery in Chinese Diabetic Patients with Obesity - Xue Zhao; Wenyan Duan; Chenglin Sun; Zhuo Li; Yujia Liu; Xianchao Xiao; Gang Wang; Xiaokun Gang; Guixia Wang (Journal of Diabetes Research)
Background. The influence of bariatric surgery on cardiovascular risks in Chinese diabetic patients remains unclear. Here, we aimed to explore the impact of Roux-en-Y gastric bypass surgery (RYGB) on cardiovascular risks in Chinese diabetic patients with obesity. Methods. Twenty Chinese patients with T2DM and obesity undergoing RYGB surgery were included in this study. Cardiovascular risk factors were measured before and 18 months after surgery. A 10-year cardiovascular risk was calculated by the UKPDS risk engine. Linear regression analysis was performed on CHD risk, stroke risk, and baseline metabolic parameters. Results. The complete remission rate of diabetes was 90% after RYGB surgery, with significant improvements in blood pressure, BMI, glucose, and lipid metabolism (P<0.05). The 10-year cardiovascular risk of coronary heart disease reduced from 13.05% to 3.81% (P=0.001) and the 10-year risk of stroke reduced from 19.66% to 14.22% (P=0.002). In subgroup analysis, Chinese diabetic patients who were women, <45 years old, with BMI < 35 kg/m2, and DM duration > 5 years, using noninsulin therapy presented more obvious improvements in the 10-year cardiovascular risk after RYGB surgery. WHR, age, LDL-C, and HbA1c were the most important factors influencing CHD or stroke risk after RYGB surgery (P<0.01). Conclusion. RYGB surgery is an effective treatment to reduce cardiovascular risk in Chinese diabetic patients with obesity.